Acetylcholinesterase Inhibition Activity of a Mixture of Methylated Depsidones from the Lichen Lobaria pulmonaria - Pejin, B.; Tommonaro, G.; Iodice, C.; Tesevic, V.; Vajs, V. (Asian Journal of Chemistry, 2012)
A phytochemical investigation conducted on a folise lichen, Lobaria pulmonaria (L.) Hoffm. (Lobariaceae), from Bosnia and Herzegovina led to a mixture of methylated depsidones which showed acetylcholinesterase inhibition activity (2 μg) in the acetylcholinesterase inhibition test on thin-layer chromatography plate. Present results indicate for the first time the potential of methylated depsidones in searching for these inhibitors, which still represent the best drugs currently available for the management of Alzheimer's disease.